Hourglass : time, memory, marriage - Shapiro, Dani (Alfred A. Knopf, 2017)
"The best-selling novelist and memoirist delivers her most intimate and powerful work: a piercing, life-affirming memoir about marriage and memory, about the frailty and elasticity of our most essential bonds, and about the accretion, over time, of both sorrow and love. Hourglass is an inquiry into how marriage is transformed by time--abraded, strengthened, shaped in miraculous and sometimes terrifying ways by accident and experience. With courage and relentless honesty, Dani Shapiro opens the door to her house, her marriage, and her heart, and invites us to witness her own marital reckoning--a reckoning in which she confronts both the life she dreamed of and the life she made, and struggles to reconcile the girl she was with the woman she has become. What are the forces that shape our most elemental bonds? How do we make lifelong commitments in the face of identities that are continuously shifting, and commit ourselves for all time when the self is so often in flux? What happens to love in the face of the unexpected, in the face of disappointment and compromise--how do we wrest beauty from imperfection, find grace in the ordinary, desire what we have rather than what we lack? Drawing on literature, poetry, philosophy, and theology, Shapiro writes gloriously of the joys and challenges of matrimonial life, in a luminous narrative that unfurls with urgent immediacy and sharp intelligence. Artful, intensely emotional work from one of our finest writers"--